Analisis preferensi siswa kelas IV terhadap penggunaan kamus pada pembelajaran bahasa Inggris di sekolah dasar - Risqa Padilasari; Erwin Rahayu Saputra; Anggit Merliana (IKIP Siliwangi, 2025)
Abstract This study aims to explore the use of dictionaries in English language learning. The background of dictionary use in English learning is based on the observation that students' learning outcomes in English are suboptimal, largely due to difficulties in understanding the meanings of English vocabulary. The utilization of dictionaries is seen as a solution to assist students in finding the meanings of unknown English vocabulary. This assertion is supported by research findings indicating that the use of dictionaries improves the quality of learning. The study employs a qualitative approach with a descriptive method. Data collection techniques include the use of questionnaires. The researcher selected Google Forms as the instrument for collecting questionnaire data. The results of this study show that 62.49% of students responded